STRATEGI KOMUNIKASI POLITIK MARUF AMIN DALAM KAMPANYE PEMILU 2019: PEMBELAJARAN UNTUK POLITIK ANTI-HOAX - Widjayanto, Febby R; Naim, Sidrotun (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
Social media feed—which is populated with text embedded in numerous forms of multimedia contents—has been a crucial battleground for politicians to situate their policy relevance to the public during election campaign. Narrative building is somewhat played out by politicians in digital space to seek an earlier assurance of their victory. This article analyses how the proponent 2019 Indonesia presidential election candidate, Joko Widodo and his running mate, Ma’ruf Amin assigns a duality of function to the anti-hoax narrative besides renders it as a firm stance they take to differ from their rival. We employ action research at the scene drawing upon the five-month period of observing one of the consultative groups to the candidate on the matter of digital campaign, and at times sharing our perspective on digital literacy and tackling disinformation. Anti-hoax narrative in the context of election turns out to be an inescapable hot topic that arguably serves as a sort of ‘free-to-use political resource’ ready to be availed of by politicians to reiterate an agenda, counterbalance and issue, or even instill a new idea regarding nationhood.